Development of matrix assessment level of safety practice for radiation risk in Malaysian radiation facilities / Hazmimi Kasim - Hazmimi , Kasim (2019)
The substantial research has investigated the nature of safety climate, and its importance as a leading indicator of safety performance, however much of this research has been conducted in Western countries, with high risk operations. This study focused on the exploratory factors of safety practice in the industrial context of Malaysian radiation facilities. Therefore, this study aims to determine the affecting factors, relationship between safety climate and risk estimate and level of safety practices. The six-factor Malaysian Safety Tool Kit (MSTK) and safety culture and practice suggested by International Atomic Energy Agency (IAEA) safety series was adopted and adapted as Malaysian radiation safety tool kit (MRSTK). An alternative nine-factor model was developed consisting of 32 items of questioning attitude, work environment, management commitment and communication, safety priority, communicative information, supportive environment, personal view, involvement and prudent approach. A repeated measure ANOVA with a Greenhouse-Geisser correction and Bonferroni post hoc test F(3.20, 994.46)= 635.80, p < 0.005, η2=0.67) indicated the difference among factors was statistically significant. Structural equation modeling (SEM) and path analysis using AMOS software was analyzing the linkages among the variables. The reliability and validity of the relationship between six safety climate factors and three determinants of risk estimate have been successfully demonstrated. The path coefficients are significant and the overall model has achieved an acceptable fit to the data. Thus, whilst these findings were consistent with common safety climate themes, it demonstrated a need to take account of individual response and organization cultural factors in the development of safety practice level assessment matrix intended for use in radiation sector. Safety practice level assessment matrix was developed through Delphi Technique with the consensus of experts’ opinion through three rounds of interviews on the level of the safety practices, safety practice criteria and indicators. Triangulation was used to ensure that there was validity in the themes that were arrived at across cases. Safety practices levels were determined. Discrepancies were discussed and adjustments were made to propose the best practices and strategies in strengthening the safety culture and practice based on the assessment matrix and other code of the data mutually arrived at. The safety practice level matrix indicated that the organization can be at different level with the same dimensions. The difference in the level is good to be indicators in controlling the radiation risk and improving the area of safety culture dimension. These findings provide valuable guidance for researchers, practitioners, regulators and policy makers for identifying the best mechanisms to strengthen the safety culture and risk management of radiation hazard in Malaysia. Keywords: Safety climate; Culture; Assessment; Safety practices matrix; Radiation safety